2005
DOI: 10.1111/j.1462-2920.2005.00863.x
|View full text |Cite
|
Sign up to set email alerts
|

Trophic regulation of Vibrio cholerae in coastal marine waters

Abstract: Cholera disease, caused by the bacterium Vibrio cholerae, afflicts hundreds of thousands worldwide each year. Endemic to aquatic environments, V. cholerae's proliferation and dynamics in marine systems are not well understood. Here, we show that under a variety of coastal seawater conditions V. cholerae remained primarily in a free-living state as opposed to attaching to particles. Growth rates of free-living V. cholerae (micro: 0.6-2.9 day(-1)) were high (similar to reported values for the bacterial assemblag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
110
1
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(124 citation statements)
references
References 38 publications
10
110
1
3
Order By: Relevance
“…following a diatom bloom Larsen et al, 2012). Moreover, V. cholerae, which is believed to be primarily attached to zooplankton (Huq et al, 1990), was also shown to respond to algal blooms by active growth in the freeliving state (Worden et al, 2006). Additionally, V. cyclotrophicus may use algal exudates as a cue to hone in on diatoms for attachment, which might be mediated by chitin contained in the diatom cell wall (Durkin et al, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…following a diatom bloom Larsen et al, 2012). Moreover, V. cholerae, which is believed to be primarily attached to zooplankton (Huq et al, 1990), was also shown to respond to algal blooms by active growth in the freeliving state (Worden et al, 2006). Additionally, V. cyclotrophicus may use algal exudates as a cue to hone in on diatoms for attachment, which might be mediated by chitin contained in the diatom cell wall (Durkin et al, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…This is reflected in low doublings per day of 0.05-0.3 for open ocean environments but up to 1-2 for coastal zones (Ducklow 2000;Crump et al 2004). However, ocean water is not homogeneous and locally confined higher growth rates can be achieved by bacteria clustered around or attached to small particles (Worden et al 2006; figure 1). Yet such relationships are rarely captured since present analysis techniques still require sampling of relatively large volumes, which average conditions and overlook spatially small nutrient inhomogeneities.…”
Section: The Life Aquatic (Ecological Parameters In the Ocean Surface)mentioning
confidence: 99%
“…Moreover, they can exploit many alternative niches and have been detected in sediments, and in and on animals; many also have pathogenic variants. In the planktonic lifestyle, these organisms probably grow in bursts, which are locally quickly erased by predation so that overall they should have higher turnover rates than other bacterioplankton (Mourino-Perez et al 2003;Worden et al 2006). There are strong indications that both Vibrio and Roseobacter sense and respond to their surroundings by several mechanisms, including: quorum-sensing systems (Gram et al 2002;Moran et al 2004); production of antibacterial compounds (Bruhn et al 2005); chemotaxis (Miller et al 2004;McCarter 2006); association with animal or algal cells (Buchan et al 2005); and rapid surface colonization (Dang & Lovell 2000;Thompson & Polz 2006).…”
Section: Genomic Consequences Of Adaptation To Environmental Variationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The assumption that bacteria capable of rapid growth show this ability only intermittently under conditions that are conducive for blooming (Yooseph et al, 2010) may therefore underestimate the trophic and biogeochemical influence of these fast-growing taxa. Instead, numbers may be kept in check by top-down control within the microbial food web (Worden et al, 2006;Ferrera et al, 2011). Selective bacterial mortality mediated through protist grazing or viral lysis (Suttle, 2007) would lessen competitive exclusion between co-occurring heterotrophs.…”
Section: Synthesismentioning
confidence: 99%